A Divided America: Good or Bad for the World? - Han, Fook Kwang (2016)
The US presidential election has shown how divided the country is. But a great power needs to be strong at home with the people and their leaders sharing a common vision of its place in the world. America needs to heal its internal divisions. For its friends abroad, a strong and stable US is good for the rest of the world.